An embedded automaton to monitor the glycolysis process in pancreatic β-cells - Ramachandran, Selvakumar; Muhammad, Rashith; Gurusamy, Poornima Devi (Acta biotheoretica, 2015)
An embedded automaton is introduced to monitor the whole glycolysis process in pancreatic β-cell and it is a hybridization of both non-deterministic finite automaton and push-down automaton. The set of irreversible and reversible reactions in the glycolysis process are related to non-deterministic finite automaton and push-down automaton respectively. The embedded automaton is used to observe the glucose metabolism with the states of acceptance and rejection. The acceptance state of the embedded automaton depicts the normal level of glycolysis and insulin secretion. The rejection state of this machine shows inhibition of glycolysis which obstructs the secretion of insulin. The subsequent low level of insulin leads to the high blood glucose level also known as hyperglycemia. In this study, the designed machine can be used to regulate the process of glycolysis through a group of regulatory glycolytic enzymes for the treatment of Diabetes mellitus at molecular level.
Published online: 5 October 2014
Gesehen am 16.06.2020